2004
DOI: 10.1074/jbc.m310042200
|View full text |Cite
|
Sign up to set email alerts
|

Rpe65 Is a Retinyl Ester Binding Protein That Presents Insoluble Substrate to the Isomerase in Retinal Pigment Epithelial Cells

Abstract: Photon capture by a rhodopsin pigment molecule induces 11-cis to all-trans isomerization of its retinaldehyde chromophore. To restore light sensitivity, the alltrans-retinaldehyde must be chemically re-isomerized by an enzyme pathway called the visual cycle. Rpe65, an abundant protein in retinal pigment epithelial (RPE) cells and a homolog of ␤-carotene dioxygenase, appears to play a role in this pathway. Rpe65 ؊/؊ knockout mice massively accumulate all-trans-retinyl esters but lack 11-cis-retinoids and rhodop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 47 publications
2
127
0
1
Order By: Relevance
“…We did not observe any effect of all-trans-retinol addition on the localization of LRAT, which remained ER-associated. Of note is that the T-REx-293 cells we used for these experiments do not express detectable levels of RPE65, a protein proposed in some studies to be a retinyl ester-binding/transport protein (42,43), yet we were still able to detect retinosome formation. The N Terminus of LRAT Is Not Conserved in All VertebratesAnalysis of the N-terminal domains of the known and putative vertebrate homologs of LRAT showed a low degree of conservation.…”
Section: The Putative C-terminal Transmembrane Domain Is Necessary Fomentioning
confidence: 77%
See 1 more Smart Citation
“…We did not observe any effect of all-trans-retinol addition on the localization of LRAT, which remained ER-associated. Of note is that the T-REx-293 cells we used for these experiments do not express detectable levels of RPE65, a protein proposed in some studies to be a retinyl ester-binding/transport protein (42,43), yet we were still able to detect retinosome formation. The N Terminus of LRAT Is Not Conserved in All VertebratesAnalysis of the N-terminal domains of the known and putative vertebrate homologs of LRAT showed a low degree of conservation.…”
Section: The Putative C-terminal Transmembrane Domain Is Necessary Fomentioning
confidence: 77%
“…The RPE65 protein is currently the only protein known to associate with retinyl esters (42,43). It has been reported that RPE65 is involved in the isomerization reaction that produces 11-cis-retinol and that retinyl esters are the preferred substrates for this reaction (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is puzzling when it is considered that RPE65 has been recently proposed to be an isomerohydrolase, the enzyme responsible for isomerization and hydrolysis of all-trans-retinyl esters to 11-cis-retinol (23-26). It should be noted that purified RPE65 has no isomerase activity (27). Further studies are required to understand the protein complex responsible for the retinoid isomerization in the RPE cells.…”
Section: Accumulation Of 13-cis-retinyl Esters In the Rpe In Rdh5−/− mentioning
confidence: 99%
“…The accumulation of retinyl esters is clearly dependent on LRAT activity (Figure 2), and these esters accumulate in Rpe65−/− mice. RPE65 was also proposed to be a retinyl esterbinding protein (27,44,45), hinting of its possible role in this process. Most insightful was the observation made by Pepperberg et al that, in normal RPE, there is a substantial exchange of all-trans-retinol with the blood circulation, whereas in Rpe65−/−mice, despite the presence of abnormally high molar levels of RPE retinyl esters, the outward movement is inhibited (43).…”
Section: Accumulation Of All-trans-retinyl Esters In the Rpementioning
confidence: 99%
See 1 more Smart Citation